Food Prices Policy: Relational Implementation of Fiqh Muamalah and Islamic Economics: Kebijakan Harga Pangan: Implementasi Hubungan Fiqh Muamalah dan Ekonomi Islam - Fuad, Zakiyyul (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2022)
There are fundamental differences between Islamic economics and Fiqh Mu‘āmalah, as well as the relationship between the two, according to Anas Zarqa and Monzer Khaf. However, according to Qadri Azizi, Islamic economics and Fiqh Mu‘āmalah are not different because there is no difference in terms of material objects. This study aims to understand the food price policy by the government as a relational implementation of Fiqh Mu‘āmalah and Islamic economics by analyzing the epistemology of Islamic economics between economics and Fiqh Mu‘āmalah, and also to understand the relation between Fiqh Mu‘āmalah and Islamic economics in food price policy by the government as a strategic study of the economy. This study is qualitative descriptive, using a content analysis tool and literature study. The results of this study are 1) There are fundamental differences between economics and Fiqh Mu‘āmalah in the epistemological aspect, which creates a scientific discipline that combines the two into Islamic Economics. 2) Fiqh Mu‘āmalah as a normative study sourced from the Alquran and hadith functions as a basis in economic cases through observation and description of phenomena. Therefore, without a touch of values and sharia norms, economics remains value-free. In terms of food price policy, factors such as economic conditions, consumer behavior, and policy implications will be a reference in normative-strategic studies for Islamic economists to sort out and determine rules that are more relevant and have greater maṣlaḥah.